Home enteral nutrition for patients with esophageal cancer undergoing esophagectomy: A systematic review and meta-analysis - Zhang, Chi; Hu, Li-Wen; Qiang, Yong; Cong, Zhuang-Zhuang; Zheng, Chao; Gu, Wen-Feng; Luo, Chao; Xie, Kai; Shen, Yi (Frontiers in Nutrition, 2022)
Introduction Home enteral nutrition (HEN) is a relatively new nutritional intervention that provides patients with EN support at home through jejunostomy or nasogastric feeding tubes. We conducted this systematic review and meta-analysis to explore the safety and effect of HEN compared with normal oral diet (NOD) in postoperative patients with esophageal cancer (EC). Methods EMBASE, Medline, Web of Science, and the Cochrane Library were used to search articles in English-language journals. The intervention effect was expressed using risk ratios (RRs) for dichotomous outcomes and mean differences (MDs) for continuous outcome measures, with 95% confidence intervals (95% CIs). The chi-square test and I-square test were used to test heterogeneity among studies. Results Four studies were eventually included in this meta-analysis. Compared with NOD, HEN has a favorable impact on postoperative body mass index (BMI) (weighted mean difference [WMD] = 0.70, 95% CI: 0.09–1.30, P = 0.02), lean body mass (LBM) (WMD = 0.76, 95% CI: 0.04–1.48, P = 0.04), and appendicular skeletal muscle mass index (ASMI) (WMD = 0.30, 95% CI: 0.02–0.58, P = 0.03). Physical function (WMD = 9.26, 95% CI: 8.00–10.53, P < 0.001), role function (WMD = 9.96, 95% CI: 8.11–11.82, P < 0.001), and social function (WMD = 8.51, 95% CI: 3.48–13.54, P = 0.001) of the HEN group were better than those of the NOD group at 3 months, and HEN could reduce the fatigue of patients (WMD = −12.73, 95% CI: −14.8 to −10.66, P < 0.001) and the incidence of postoperative pneumonia (RR = 0.53, 95% CI: 0.34–0.81, P = 0.004). There was no significant difference in albumin between HEN and NOD groups (WMD = 0.05, 95% CI: −0.03 to 0.13, P = 0.20). Conclusion HEN improved nutritional status and quality of life (QOL) in postoperative patients with EC and reduced fatigue and the incidence of postoperative pneumonia. All in all, the results of our meta-analysis support the use of HEN after esophagectomy.